Integrating the Concept of Dynamic Capabilities to Strengthen School Performance Assessment Indicators: A Systematic Literature Review - Teguh Trianung Djoko Susanto; Siti Zulaikha; Sultan Abdullah (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
This study is motivated by the limitations of the school performance assessment system in Indonesia, which remains largely administrative and compliance-oriented toward the National Education Standards (SNP). Such an approach fails to adequately reflect schools’ adaptive and innovative capacities in responding to policy dynamics and the rapid development of educational technology. The purpose of this research is to analyze the application of dynamic capability principles in school performance assessment, to develop a dynamic capability–based assessment model suited to the Indonesian educational context, and to evaluate its effectiveness in enhancing schools’ adaptive and innovative abilities. The research employs a Systematic Literature Review (SLR) combined with bibliometric analysis using the VOSviewer software to map the interrelations between the concepts of dynamic capabilities and school performance. Data were collected from scholarly publications published between 2010 and 2025 through the Google Scholar database and processed using Publish or Perish. The findings reveal three major clusters demonstrating a strong relationship among dynamic capabilities, innovation, and school performance. The developed assessment model emphasizes three core dimensions of dynamic capabilities sensing, seizing, and reconfiguring which are proven to be relevant for assessing schools’ adaptive and innovative capacities. In conclusion, integrating the concept of dynamic capabilities into the school performance assessment system can enhance the effectiveness of educational quality evaluation, making it more sustainability-oriented and supportive of organizational transformation.